(untitled) (International Journal of Ayurveda and Pharma Research, 2022)
Menopausal syndrome is a grouping of signs and symptoms associated with menopause. In Ayurveda, menopause is referred to as ’Rajonivrutti’ (and menopausal syndrome as Rajonivruttianubandhaja vyadhies). Menopause’s long-term risks include osteoporosis, cardiac problems, and Alzheimer’s disease. Aims and objective: To study the Pharmacognostic, Phytochemical and HPTLC of Vayasthapana Gana Choorna and Vayasthapana Ghrita. Material and methods: Pharmacognostic, phytochemical and HPTLC of Vayasthapana Gana Choorna and Vayasthapana Ghrita have been carried out as per standard protocol. Result: Vayasthapana Gana Choorna showed the presence of mesocarp, asicular crystals, stone cells, scleroids, brown content, starch grains, colencyma cells, rhomboidal crystals, pitted vessels, parenchyma cells, simple trichome. Phytochemical parameters showed refractive index 1.3660, specific gravity 0.913, acid value 1.285, iodine value 212.1085 and in HPTLC, Methanol extract of Vayasthapana Ghrita at 254nm showed 6 spots and at 366nm 2 spots whereas in methanol extract of Vayasthapana Gana Choorna at 254nm 5 spots and in 366nm 4 spots were present. Conclusion: The applied pharmacognostic and HPTLC method has been shown to be selective, linear, precise and accurate. The method will be useful for quality control of the raw material and pharmaceutical preparations.